Tettigetta carayoni Boulard (Hemiptera: Cicadidae) from Crete, faunistic data and first description of its song - Trilar, Tomi (Acta entomologica slovenica (Ljubljana), 2010)
Using recording equipment for sonic and ultrasonic range we recorded the calling song of Tettigetta carayoni Boulard 1982, which is endemic to the Greek island of Crete (Kriti). It is widely distributed and common species from the seacoast to the mountains up to 1500 m above sea level. Nevertheless,the song of this species has not been described until now. The calling song structure is characteristic and easily distinguishable from the songs of related cicadas. Typical for the calling song is very fast repetitionrate with 7 to 11 echemes per second. It consists of two parts, together forming a complete song with usual duration of many minutes. The monotonous part is a regular repetition of echemes with medium length, while rhythmic part consists of series with 2 to 4 very short echemes followed by one longer echeme. The monotonous part and rhythmic part can exchange either on a regular basis either one part is very long and can be randomly interrupted with a few echemes from opposite part. Studied was also the microstructure of the song, which shows 4-click units and consequently the stepwise distribution of the echeme duration. The song contains frequencies from 6 to 20 kHz with a maximum between 10.8 and 14.7 kHz. This species specific calling song pattern is compared with songs of other European cicadas.
Keywords: Crete; entomologija; favna; Kreta; škržadi